L'AEROFOTOTECA NAZIONALE RACCONTA.... Pianura Pontina, 17 marzo 1944: la "slicing run” del tenente Dolk - Brozzi, Paolo (GEOmedia, 2020)
On March 17, 1944 Lt. Carl E. Dolk of the USA Air Force took over the Pontine plain to the E of Anzio a number of aerial photos in what was called in military jargon a "dicer run". This was a highly hazardous low altitude flight that would enable the Allied command to decide how to overcome the German barrage. This set of photos is kept today by the Aerofototeca Nazionale in Rome.